PENGARUH KONSENTRASI INDUSTRI TERHADAP KINERJA INDUSTRI GARAM Dl KOTA PALEMBANG - Nyayu Fatimah; Bernadette Robiani; Abbas Effendi (Jurnal Ekonomi Pembangunan, 2004)
This research is intended to analyze the effect of industrial concentration on industrial Performance of Salt Industry in Palembang. Industrial concentration is described  by concentration ratio of two largest firms (CR2) of output value. Growth wage rate is used to measure wage performance of Salt Industry in Palembang over aperiod  1994-2003. Industrial  Organization  Theory and  Wage Theoryare used to analyze  the performance  of salt industry during the years of 1994-2003. The data that used in this research are secondary data and primary data. The technique analysis used in this research is simple linier regression model. The results indicate that the concentration ratio of two largest firms (CR2) for output value effect on growth wage rate is equal to 10,7 percent and corelating between both variables is equal to 32,6 percent. The statistic   test   (t-test) indicates that industrial concentration effect on the industrial performances is significant. Therefore it can be concluded that industrial concentration which is measured by concentration ratio output value and industrial performance which is measured by growth wage rate have a positive relationship. Keywords: Industry, Concentration, Performance